Development of the Mobile Vision Enhancement System (moves) for sight-assist mechanism / Mohd Rizman Sultan Mohd ... [et al.] - Sultan Mohd, Mohd Rizman; Mazlan, Muhammad Akmal; Johari, Juliana; Ahmat Ruslan, Fazlina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Vision-related diseases can have various effects on the human eye, ranging from minor sight distractions to the most severe cases of total blindness. There are multiple medical treatments available for the patient, as well as alternative methods, including wearable tools, to assist the patient in their daily routine activities. The most commonly used tool is the guide stick, which requires the user to hold it, thus limiting its flexibility. The technology-aided system also depends on the power supply, which also adds to the limitation. Inspired by the solar-based system, this project applies the portable sight-assist system, which is easy to use and comes with wearable design ideas. The proposed Mobile Vision Enhancement System (MOVES) is a solar-powered system that assists the user in detecting obstacles in their path. It is designed to fit in the hat worn by the user. The MOVES is designed using the Arduino Nano Microcontroller Board with a compatible poly-crystalline solar panel for solar-powered systems, an ultrasonic sensor for obstacle detection, and a buzzer for the alert system. The main objectives of the headwear design are that the system operates by using a solar panel, which is practical to place at the top, and the user does not have to hold it by hand, making it a hands-free system. The MOVES system has been tested in controlled environments with various obstacle placements. This is important, as the system must be able to detect any obstacle in the user’s pathway to avoid collisions and endanger the user. Based on the test, the MOVES had proven to be useful in assisting the user in detecting obstacles and helping the user in avoiding any obstacle in their path, with a mean relative error of less than 5%. Thus, MOVES is proposed as an alternative sight-assist system to be used by a visually impaired person